2009
DOI: 10.5194/nhess-9-1551-2009
|View full text |Cite
|
Sign up to set email alerts
|

A pre seismic radio anomaly revealed in the area where the Abruzzo earthquake (<i>M</i>=6.3) occurred on 6 April 2009

Abstract: A pre seismic radio anomaly revealed in the area where the Abruzzo earthquake (M=6.3) occurred on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 18 publications
4
29
1
Order By: Relevance
“…Two are the main types of precursors involved: radon emission and foreshocks. However, the only scientifically documented precursor so far was described by Biagi et al (2009) who reported on a radio emission in association to that earthquake. In this paper, we analyze a posteriori the seismicity before and after the L'Aquila earthquake, with the aim to detect foreshock signals bearing precursory value for the prediction of the mainshock.…”
Section: Introductionmentioning
confidence: 99%
“…Two are the main types of precursors involved: radon emission and foreshocks. However, the only scientifically documented precursor so far was described by Biagi et al (2009) who reported on a radio emission in association to that earthquake. In this paper, we analyze a posteriori the seismicity before and after the L'Aquila earthquake, with the aim to detect foreshock signals bearing precursory value for the prediction of the mainshock.…”
Section: Introductionmentioning
confidence: 99%
“…4, and is expected to monitor signals emitted from active transmitters to study the seismic activity in the WENP region. In fact, the relevant issue when choosing a transmitter is that the radio path from the transmitter to the receiver crosses the epicentral area, Biagi et al (2008Biagi et al ( , 2009, so three transmitters out of the ten being ex- Funchal (Madeira-Portugal), Ceuta (Spain). Figure 5 shows the location of the mentioned emitters and the receiver.…”
Section: Observation Of Vlf/lf Radio Signalsmentioning
confidence: 99%
“…Thus, two seismo-electromagnetic phenomena (SEM) will be considered: ULF electromagnetic field emissions, Telesca et al (2008), and VLF/LF radio broadcastings, Biagi et al (2009). With respect to the ULF measurements, magnetometers are planned to be installed in the South of Iberian Peninsula supported by the existing networks of seismic research and a portable ULF station is also under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper, we excluded the possibility that the anomaly was related to the transmitting station, because in the considered period the receivers in Bari (southern Italy) and in Bucharest (Romania) received normally the same signal ( Fig. 6 in Biagi et al, 2009). We attributed the anomaly (drop) in the radio Correspondence to: P. F. Biagi (biagi@fisica.uniba.it) signal to a defocusing of the signal radiated by the RMC station and we proposed that this was evidence for a precursor of the L'Aquila earthquake.…”
Section: Facts and Commentmentioning
confidence: 99%